In-situ catalytic pyrolysis of spirulina platensis residue (SPR): Effect of temperature and amount of C12-4 catalyst on product yield - Siti Jamilatun; Ratih Mahardhika; Imelda Ika Nurshinta; Lukhi Mulia Sithopyta (Jurnal Rekayasa Proses, 2021)
Currently, dependence on fossil energy, especially petroleum, is still high at 96% of the total consumption. One solution to overcome fossil energy consumption is processing alternative energy sources derived from microalgae biomass. This study aims to study the pyrolysis of microalgae with the addition of the C12-4 (Cr2O3+Fe2O3+C+CuO+promoter) catalyst. The biomass used in this study was Spirulina platensis residue (SPR). This study used a fixed bed reactor with an outer diameter of 44 mm, an inner diameter of 40 mm, and a total reactor height of 600 mm. The C12-4 was mixed fifty grams of SPR with a particle size of 100 mesh with a ratio variation of 5, 10, and 15 wt.%. The feed mixture was placed in the reactor (in-situ), and the reactor was tightly closed. The nickel-wire heater wrapped around the reactor wall was employed. The pyrolysis heating rate was 24.33 °C/min on average, and the temperatures were varied as 300, 400, 500, 550, and 600 °C. The research found that the optimum temperature conditions without and with the catalyst to produce bio-oil were different. The pyrolysis without any catalyst (500 ⁰C), with a catalyst of 5 wt.% (500 ⁰C), 10 wt.% (400 ⁰C), and 15 wt.% (550 ⁰C) produced the bio-oil yield of 15.00, 17.92, 16.78 and 16.54, respectively. The use of 5, 10, and 15 wt.% catalysts increased the water phase yield. The char yield was influenced by the amount of catalyst only at 300 ⁰C; i.e., the more catalysts, the less char yield. The pyrolysis without any catalysts produced the highest gas product. A catalyst significantly increased the pyrolysis conversion from 48.69 (without catalyst) to 62.46% (15. wt.% catalyst) at a temperature of 300 ⁰C. The optimum conditions for producing the best bio-oil were at 600 °C and 10 wt.% of catalysts, which resulted in an O/C ratio of 0.14.